Development of numerical methods and virtual tests for cyclic durability by finite element method - Papirovskiy, A.; Alekseev, S.; Tarasov, A.; Borovkov, A. (Peter the Great St. Petersburg Polytechnic University, 2019)
This paper deals with the issue of fatigue failure of materials. The process of
generation of fatigue properties for the steel 08PS is described and obtained in the laboratory.
The technique of conducting virtual tests for cyclic durability for vehicles is proposed. Virtual
tests for cyclic durability by using the finite element method on the example of an off-road car
body are performed.